Simulation and experimental studies of induction hardening behavior of a new medium-carbon, low-alloy wear resistance steel. Issue 1 (17th January 2020) - Javaheri, Vahid; Asperheim, John Inge; Grande, Bjørnar; Kolli, Satish; Porter, David
Abstract : Purpose: The purpose of this work is to determine the induction hardening behavior of a new steel composition. For this purpose, Flux2D commercial software together with a Gleeble thermomechanical simulator has been used to numerically and physically simulate the material properties profile of an induction hardened slurry transportation pipe made of a recently developed 0.4 Wt.% C, Nb-microalloyed steel. Design/methodology/approach: Flux 2D commercial software together with a Gleeble thermomechanical simulator machine has been used to predict the induction behavior of the studied material. After calculating the thermal history of a 400 mm diameter, 10 mm thick pipe at various positions through the thickness, different heating and cooling paths were physically simulated using the Gleeble machine to predict the through thickness material microstructure and hardness profiles. Finding: The results showed that by coupling a phase transformation model considering the effect of heating rate on the austenite transformation temperatures which allows calculations for arbitrary cooling paths with calculated induction heating and quenching thermal cycles, it has been possible to design induction hardening parameters for a slurry transport pipe material. Originality/value: The composition used in this research as well as the methodology approach is designed at this work.